Pamiparib is a potent and selective PARP inhibitor with unique potential for the treatment of brain tumor - Xiong, Yao; Guo, Yin; Liu, Ye; Wang, Hexiang; Gong, Wenfeng; Liu, Yong; Wang, Xing; Gao, Yajuan; Yu, Fenglong; Su, Dan; Wang, Fan; Zhu, Yutong; et al. (Neoplasia (New York, N.Y.), 2020)
Pamiparib, an investigational Poly (ADP-ribose) polymerase (PARP) inhibitor in clinical development, demonstrates excellent selectivity for both PARP1 and PARP2, and superb anti-proliferation activities in tumor cell lines with BRCA1/2 mutations or HR pathway deficiency (HRD). Pamiparib has good bioavailability and is 16-fold more potent than olaparib in an efficacy study using BRCA1 mutated MDA-MB-436 breast cancer xenograft model. Pamiparib also shows strong anti-tumor synergy with temozolomide (TMZ), a DNA alkylating agent used to treat brain tumors. Compared to other PARP inhibitors, pamiparib demonstrated improved penetration across the blood brain barrier (BBB) in mice. Oral administration of pamiparib at a dose as low as 3 mg/kg is sufficient to abrogate PARylation in brain tumor tissues. In SCLC-derived, TMZ-resistant H209 intracranial xenograft model, combination of pamiparib with TMZ overcomes its resistance and shows significant tumor inhibitory effects and prolonged life span. Our data suggests that combination of pamiparib with TMZ has unique potential for treatment of brain tumors. Currently, the combination therapy of pamiparib with TMZ is evaluated in clinical trial [NCT03150862].